Optimization of DNA Isolation Dried Leaf Samples of Endangered Plants Dipterocarpus cinereus - Ruri Fitriyani; Robiansyah, Iyan; Achyar, Afifatul (Tropical Genetics, 2022)
Dipterocarpus cinereus (Lagan bras) is an endemic tree of Mursala, a small island in Central Tapanuli, North Sumatra. Lagan bras is a tree that has good quality for shipbuilding or construction materials. This plant has a critical status by the IUCN Red List 2020 so that conservation efforts need to be carried out. Conservation efforts are still limited to the status of conservation, ecology and distribution as well as vegetative propagation while molecular studies have never been carried out. Therefore, it is necessary to know the optimum DNA isolation method because DNA quality is very important as a determinant of the success of molecular analyzes such as PCR. Various techniques can be used to isolate DNA, depending on the type of plant used. Each type of plant contains different secondary metabolite compounds that require an optimum isolation method. This study aims to obtain the optimum DNA isolation method and produce good quality genomic DNA from the dried plant Dipterocarpus cinereus from the LIPI Plant Conservation Research Center and Botanical Gardens collection. This research was conducted at the Genetics and Biotechnology Laboratory, State University of Padang in October 2021. The DNA isolation method used was the modified CTAB method with variations in leaf size, the use of PVP, and grinding with and without liquid nitrogen as well as the Promega and Qiagen isolation kit methods. The results showed that a large quantity of DNA and high quality DNA could be produced in plant samples by modifying DNA isolation using the Cetyl Trimethyl Ammonium Bromide (CTAB) method as well as the addition of polyvinylpolypyrrolidone (PVP) antioxidants and the use of liquid nitrogen with a leaf size of 2x2 cm.